Editorial: The 22nd International Conference on Control, Automation, and Systems (ICCAS 2022) - Ahn, Hyo-Sung (International journal of control, automation, and systems, 2023)
This special section is dedicated to the papers selected from the 22nd International Conference on Control, Automation, and Systems (ICCAS 2022), held in Busan BEXCO, Korea, from November 27 to December 1, 2022. The selectionprocess was overseen by the award committee chair, Prof. Chul-Goo Kang, who recommended a total of ten papers: five finalist papers for the Best Paper Award and five finalist papers for the Best Student Paper Award. Following Prof. Kang’s recommendations, the authors of these selected papers were invited to submit an extended version of their conference papers for review at the International Journal of Control, Automation, and Systems (IJCAS). The guidelines required the authors to augment their papers by at least 35% from the original conference version and include additional results. Moreover, authors were asked to cite their respective ICCAS papers in the journal version while addressingany notable differences between the two versions. The submitted papers underwent an expedited review process conducted by a panel of distinguished reviewers. Despite the fast-track handling, the reviews were conducted with utmost rigor to ensure the quality and excellence of the selected papers. Subsequently, the following four papers were chosen for publication:1. “Koopman Operator-based Model Identification and Control for Automated Driving Vehicle” by Jin Sung Kim, Ying Shuai Quan, and Chung Choo Chung. 2. “Adaptive Online Steering Efficiency Coefficient Estimation for Enhanced Terrain Motion Control in Four-wheeled Skid-steering Mobile Robots” by Le Bao, Kai Li, Changsoo Han, Kyoosik Shin, and Wansoo Kim. 3. “A Model Predictive Voltage Control for Dual-active-bridge DC-DC Converter Using Generalized Averaging Model” by Ngoc-Duc Nguyen and Young Il Lee. 4. “ASAD: Autonomous Seismic Acquisition Device” by Grigoriy Yashin, Valerii Serpiva, Artem Timoshenko, Nikita Mikhailovskiy, Anton Egorov, and Pavel Golikov. Moving forward, the editorial board of IJCAS plans to continue its efforts in identifying exceptional papers from future editions of The International Conference on Control, Automation, and Systems for potential publication at IJCAS. KCI Citation Count: 0